Toma de decisión para inversión en acciones de avianca holdings s.a. o copa holding s.a. a través, del estudio del índice de volatilidad de los precios en el mercado. (2019)
Trading has became in a fundamental form for getting into the bursátil market, technology in now available for everibody, the access to a world of finantial possibilities with AC, forex, options,etc. With the help of indicators analysis it is possible to create our personal marketing strategies. The main objetive of these paper is design an strategy based in the volatility analysis of the prices in order to determinate the buy options and sell options in the shares in The New York Stock Exchange from Avianca Holdings S.A. o Copa holding S.A. enterprises. Also, the relationship between the volatility and share prices behaviour in high volatility. Based an the results done with simulated graphics from ProRealTime, an excellent strategy ehit huge potential is obtained, but it is not perfect due to the simple intructions, but what all this the conclusion will be to study deep into the shares market and in the trading strategies. Key words: trading, stock market, shares, indicators, buy options, sell options.